2020
DOI: 10.1021/acs.est.0c01849
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Pollutants in Proglacial Lake Sediments: Impacts of Glacial Meltwater and Anthropogenic Activities

Abstract: With global warming, the melting of glaciers can result in the release of pollutants into the environment. For remote Alpine lakes, both atmosphere-deposited anthropogenic pollutants and glacier-released pollutants can eventually sink in the sediment. To date, there has, to the best of our knowledge, been no attempt at quantifying the contributions of these processes to the accumulation of pollutants in glacial lake sediment. To fill this gap, a semienclosed proglacial lake located in the southern Tibetan Plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 61 publications
(137 reference statements)
1
17
0
Order By: Relevance
“…For remote alpine lakes, likewise, the atmospheric deposited Hg and POPs released by glaciers can end up sinking into the sediments. [172][173][174] To ll this critical research gap, Zhu et al 103 selected a semi-closed preglacial lake in the southern part of the TP and reported profound anthropogenic contributions ranging from <10% in the 1850s to >40% aer the 1980s. Moreover, the observed contribution from meltwater release in the 1950s was 61%.…”
Section: Accumulation Of Hg and Pops In Lake Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For remote alpine lakes, likewise, the atmospheric deposited Hg and POPs released by glaciers can end up sinking into the sediments. [172][173][174] To ll this critical research gap, Zhu et al 103 selected a semi-closed preglacial lake in the southern part of the TP and reported profound anthropogenic contributions ranging from <10% in the 1850s to >40% aer the 1980s. Moreover, the observed contribution from meltwater release in the 1950s was 61%.…”
Section: Accumulation Of Hg and Pops In Lake Sedimentsmentioning
confidence: 99%
“…Over the past two decades, 90% of the pollutant deposition in the sediments can be attributed to the combined action of major pollutant discharge and glacial release. 103…”
Section: Accumulation Of Hg and Pops In Lake Sedimentsmentioning
confidence: 99%
“…As BC is chemically inert in the lake sediment cores, it can serve as an archive and reliable indicator to investigate the source and transport of BC in the past (Han et al, 2012). The BC investigation from lake sediment cores over the plateau revealed an increasing trend of BC concurrent with increased anthropogenic emissions since the 1950s (Cong et al, 2013;Han et al, 2015;Neupane et al, 2019;Zhu et al, 2020) and suggested that BC deposition in recent decades has increased about 2-3-fold compared to the background level.…”
Section: Introductionmentioning
confidence: 99%
“…As BC is chemically inert in the lake sediment cores, it can serve as an archive and reliable indicator to investigate the source and transport of BC in the past (Han et al, 2012). The BC investigation from lake sediment cores over the plateau revealed an increasing trend of BC concurrent with increased anthropogenic emissions since the 1950s (Cong et al, 2013;Han et al, 2015;Neupane et al, 2019;Zhu et al, 2020), and suggested that BC deposition in recent decades have increased about 2−3 fold compared to the background level.…”
Section: Introductionmentioning
confidence: 99%